L’expérience de métier : le catalyseur des conceptions de l’enseignement en formation professionnelle au Québec - Frédéric Deschenaux; Chantal Roussel (Recherches en Éducation)
In Quebec, several studies document the transition experienced by teachers of vocational training. The first section of the article lays out three points emerging from these works, highlighting that little is known about their conceptions of teaching, yet necessarily mobilized in this transition. The exploration of these conceptions is therefore the general objective of this article. The 32 interviews with teachers are analyzed. For them, a good teacher is someone who can adapt, listen and who demonstrates a technical competence. The fact that these teachers live an intense transition from the practice of their profession and education inevitably color their approach of the new role they will play.